Indigenous standpoint theory as a theoretical framework for decolonizing social science health research with American Indian communities. (December 2021) - Cox, Genevieve R; FireMoon, Paula; Anastario, Michael P; Ricker, Adriann; Escarcega-Growing Thunder, Ramey; Baldwin, Julie A; Rink, Elizabeth
Theoretical frameworks rooted in Western knowledge claims utilized for public health research in the social sciences are not inclusive of American Indian communities. Developed by Indigenous researchers, Indigenous standpoint theory builds from and moves beyond Western theoretical frameworks. We argue that using Indigenous standpoint theory in partnership with American Indian communities works to decolonize research related to American Indian health in the social sciences and combats the effects of colonization in three ways. First, Indigenous standpoint theory aids in interpreting how the intersections unique to American Indians including the effects of colonization, tribal and other identities, and cultural context are linked to structural inequalities for American Indian communities. Second, Indigenous standpoint theory integrates Indigenous ways of knowing with Western research orientations and methodologies in a collaborative process that works to decolonize social science research for American Indians. Third, Indigenous standpoint theory promotes direct application of research benefits to American Indian communities.